2012
DOI: 10.3109/15412555.2011.647131
|View full text |Cite
|
Sign up to set email alerts
|

Anemia is a Mortality Predictor in Hospitalized Patients for COPD Exacerbation

Abstract: Anemia and previous exacerbations were independent predictors of mortality after one year in patients hospitalized for AECOPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 37 publications
4
50
2
1
Order By: Relevance
“…The prevalence of anemia in this study exceeds the prevalence found by Martinez-Rivera et al19 A possible explanation is the exclusion from that study of patients with certain comorbidities or severe acute disease, both of which are associated with low hemoglobin. In contrast, a higher prevalence than ours was found in Silverberg et al31 Possible explanations are a different case mix where, for example, diabetes was twice as frequent as in our population and the exclusion from our study of patients admitted previously for AECOPD.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The prevalence of anemia in this study exceeds the prevalence found by Martinez-Rivera et al19 A possible explanation is the exclusion from that study of patients with certain comorbidities or severe acute disease, both of which are associated with low hemoglobin. In contrast, a higher prevalence than ours was found in Silverberg et al31 Possible explanations are a different case mix where, for example, diabetes was twice as frequent as in our population and the exclusion from our study of patients admitted previously for AECOPD.…”
Section: Discussioncontrasting
confidence: 79%
“…Though this association is known in stable-phase COPD patients,34 to our knowledge only one small study has examined the association between anemia and long-term mortality in patients admitted to hospital with AECOPD 19. The association found with hemoglobin <130 g/L in that population was very strong, with an odds ratio for death within a year after admission of 5.9.…”
Section: Discussionmentioning
confidence: 93%
“…In a retrospective study of a series of patients with various disorders who were discharged from hospital, anaemia prevalence among COPD patients was 23.1 %, comparable with the one among individuals with heart failure [23]. In a longitudinal study by Almagro et al [14], anaemia prevalence among hospitalized patients for AE-COPD was 19.3 %, whereas other authors have reported even higher frequencies, ranging from 26 % to 33 % [15,28]. Hospitalacquired anaemia [29] is a unique entity affecting patients with various disorders who are admitted in hospital; nevertheless, during AECOPD, the burst of systemic inflammation is a factor further inhibiting erythropoiesis, as described below in detail.…”
mentioning
confidence: 72%
“…COPD combined with anemia was more common than polycythemia in our study. The incidence of anemia in COPD was between 10% and 15%, and anemia increases the severity of dyspnea, reduces exercise tolerance, and increases risk of death 32,33 . Barba et al studied 289,077 hospitalized AECOPD patients and found 9.8% of cases coexisted with anemia, and anemia increased the risk of readmission by 25% in the two-year study period 34 .…”
Section: Discussionmentioning
confidence: 99%